The Analysis of Game Usage for Senior High School Students to Improve Their Vocabulary Mastery - Hafidz Tresna Yudha; Berlinda Mandasari (fsip.teknokrat.ac.id, 2021)
Vocabulary plays an important role in learning English. Learning vocabulary in English is not easy, especially for students in vocational high school. In addition, they have special characteristics that are very different from adults. With emphasis on these different characteristics, it can be concluded that teachers who teach vocational learners have a challenging task to be able to motivate them in the learning process. In this case, teachers must be more creative and keep their students away from boredom while learning English vocabulary. They must prepare material to be given to students and also choose appropriate techniques to use. By doing these things, they can make students have a great interest in the learning process. They must be able to choose and use teaching techniques that can make the learning process more fun, interesting, and exciting for students. One such technique is to use games in the classroom. Using games can provide many benefits for teachers and students.This research aimed at identifying students’ improvement on their vocabulary mastery after learning English using game. The participant of this study is students of junior high school in Lampung province. Data gathered through questionnaire. The data then analyzed by using Creswell method. The result shows that using games in learning English vocabulary is very effective, because using games is very fun and matches the characteristics of children as learners.